Counseling of Zakat Management in Daarul Ilmi Islamic Boarding School Cipeundeuy - Abdul Rojak, Encep; ., Mujahid; Ahmad Nasir, Malki; Farrih Izadi, Fariz (KnE Social Sciences, 2023)
The zakat management system according to Law (UU) Number 23 of 2011 is categorized into two, the first is an institution created by the Government, namely the National Amil Zakat Agency (BAZNAS) and the second is an institution built on the initiative of the community or association, namely the Amil Zakat Institution (Lembaga Amil Zakat) LAZ. The zakat law stipulates that LAZ which is formed at the initiative of the community by assisting the collection of zakat, its distribution, utilization, and formation must obtain permission from the minister or an official appointed by the minister. Article 38 of the Zakat Law emphasizes that the management of zakat by the community must go through a mechanism that has been regulated, so it is not permissible to establish an Amil Zakat body without the permission of the authorized party (government). The Daarul Ilmi Integrated Islamic Boarding School as one of the foundations located in Cipeundeuy, West Bandung Regency has a zakat empowerment program that has been implemented for 5 consecutive years. This service aims to see whether this institution is in accordance with the Sharia and zakat laws in its management or not. In principle, the management of zakat is in accordance with Sharia rules, but there are still shortcomings in the licensing aspect, namely, this institution has not registered as a LAZ. Extension activities and assistance to human resources (HR) in Islamic boarding schools are very necessary to achieve the desired goal, namely, the legality of the Zakat Management Institution. It is hoped that after obtaining legality, the management of zakat, infaq, and alms can be developed and gain the trust of the wider community, so that the benefits of zakat can be felt by people in need, especially for students and the community around Islamic boarding schools. Keywords: legality, zakat management, Islamic boarding school